Changes in glacier area and volume in Terskey Ala-Too Range in the second half of XX century - S. S. Kutuzov (Лëд и снег, 2015)
Changes in the extent of glaciers and rates of glacier termini retreat in the eastern Terskey-Alatoo Range, the Tien Shan Mountains, Central Asia have been evaluated using the remote sensing techniques. Changes in the extent of 109 glaciers between 1965, 1990 and 2003 have been estimated through the delineation of glacier outlines on the topographic maps, Landsat TM and ASTER imagery for 1965, 1990 and 2003 respectively. Glacier surface area has decreased by 12.6% of the 1965 value between 1965 and 2003. Detailed mapping of 10 glaciers using historical maps and aerial photographs from the 1943–1977 period, has enabled glacier extent variations over the 20th century to be identified with a higher temporal resolution. Glacial retreat was slow in the early 20th century but increased considerably between 1943 and 1956 and then again after 1977. The post-1990 period has been marked by the most rapid glacier retreat since the end of the LIA. For the selected 13 glaciers volume reduction has been evaluated using a time step digital elevation models. DEM obtained from the 1:25 000 topographic maps of 1965 and 1977 were compared to SRTM data. The observed changes in the extent of glaciers are in line with the observed climatic warming. The regional weather stations have revealed a strong climatic warming during the ablation season since the 1950s at a rate of 0.02–0.03 oC a-¹. At the higher elevations in the study area represented by the Tien Shan meteorological station, the summer warming was accompanied by negative anomalies in annual precipitation in the 1990s enhancing glacier retreat. However, trends in precipitation in the post-1997 period cannot be evaluated due to the change in observational practices at this station. Neither station in the study area exhibits significant long-term trends in precipitation.